NILAI PENDIDIKAN KARAKTER DALAM TAFSIR QS. LUQMAN AYAT 12–19 DAN IMPLIKASINYA TERHADAP LAYANAN BK DI SEKOLAH - Herwantoro; Emmi Kholilah Harahap; Rifanto Ridwan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character education has become an important concern in the Indonesian education system due to various moral issues among students, such as low discipline, lack of politeness, bullying, intolerance, and weak social responsibility. From an Islamic perspective, character education has a strong foundation in the Qur’an, particularly in QS. Luqman verses 12–19, which contain the advice of Luqman al-Hakim to his son. This study aims to analyze the values of character education in the interpretation of QS. Luqman verses 12–19 and their implications for Guidance and Counseling (GC) services in schools. The study employs a qualitative approach using library research. Primary data were obtained from the Qur’an and tafsir literature, particularly Tafsir Al-Misbah by M. Quraish Shihab, Tafsir Ibn Kathir, and Tafsir Al-Azhar by Hamka, while secondary data were collected from relevant journals, books, and scientific articles. Data analysis was conducted through content analysis using a descriptive-analytical approach. The findings reveal that QS. Luqman verses 12–19 contain character values such as religiosity, gratitude, monotheism (tawhid), respect for parents, responsibility, worship discipline, enjoining good and forbidding evil, patience, humility, simplicity, communication ethics, and social concern. These values are relevant to be implemented in Guidance and Counseling services to develop students with strong character, noble morals, and balanced spiritual and social competencies in the digital era.